The little secret that can change your life : if you win the rat race, you're still a rat - Davis, Joann, 1953- (2005)
With a light heart and in the nicest, most insightful way, Joann Davis invites us to stop running around in circles. If we stop working for the cheese at the end of the maze, for the biggest toys at the end of the day, who knows what we could accomplish or how we might feel? This little book is nothing less than a game plan for creating a life that counts. In the tradition of Robert Fulghum, The Little Secret That Can Change Your Life* is a collection of short inspirational essays designed to help readers discover the path to a more meaningful life, one that is less about running the modern rat race of workaholism, consumerism, debt, and frustration. The book suggests that a more rewarding way of living comes when we realize that beneath the surface of life is a spiritual economy made up of virtues and values. Money and material things matter, but they aren't everything. We must be careful not to gain the world and lose our souls. "Our inner world is ours to make of what we choose. Magnificent changes can radiate out of every human heart if we so desire. So then, if you are open, brave, and willing to take the challenge, read on. See if you don't agree that there's much more to life than winning the rat race." If every person who reads this book chooses one way to leave the rat race and passes the idea to just one other person, in no time at all our national priorities could change. Children could become more important than money. Virtue could become its own reward. Corporate greed could become passe. There are rules for rats -- Bite off more than you can chew. Act as if enough isn't -- ever. View life as part of work, instead of work as a part of life. Follow them all, win the race, and you'll still be -- a rat! There are rules for mice -- No fighting, no biting. You scratch my back, I'll scratch yours. If you can't fight 'em, lick 'em. "synopsis" may belong to another edition of this title.